Attitude Of Mothers After Childbirth Who Abstain From Eating In Ngebrak Village , Subdistrict Of Gampengrejo, Kediri Regency - Is Fadhillah (Jurnal Keperawatan, 2018)
After the childbirth process, a mother is in the period after childbirth in which all of the genetalia have not been recovered as they were before the pregnancy. It requires much high nutrious foods with enough calory protein, fluid and fruits as well. But several factors in which one of them is from cultural aspect has influenced the changing of their attitude to abstain from eating. Obviously, this phenomenon can influence their health and recovery period after the childbirth indirectly. The object of this study is to find out the attitude of those mothers after the childbirth who abstain from eating in Ngebrak village, Subdistrict of Ringinrejo, Kediri Regency. The reseach design includes the cross sectional. The population is all mothers after childbirth who abstain from eating in Ngebrak village, Subdistrict of Ringinrejo, Kediri Regency. It is done toward the total sampling. The data is processed by analyzing the percentage. As the result, it is found out most respondents have three reasons to abstain of eating. There are 12 respondents (60%) and almost half of them have three kinds of prohibited meals. There are 7 respondents (35%) from the total of 20 respondents. The conclusion is most of those mothers after childbirth who abstain from eating is they do that because of beauty reason, cultural heredetary, elder people’s advice as well as their own belief and knowledge about abstaining as far as they know. Most avoided meals are animal protein. What would be better to do on this matter is by giving them information continously about commiting abstain from eating since it is still found nowdays. And most of them have more than a single reason to do that. Keywords: attitude, mother after childbirth, abstain from eating.